Effect of single and multiple AM fungal inoculants on the growth parameter of Ocimum basilicum var. Thysiflora Benth - Yeasmin, T; Puttaradder, J; Lakshman, HC (Journal of Bio-Science, 2018)
Abstract not available J. bio-sci. 23: 89-91, 2015